2020
DOI: 10.3389/fimmu.2020.01716
|View full text |Cite
|
Sign up to set email alerts
|

Differential Accumulation and Activation of Monocyte and Dendritic Cell Subsets in Inflamed Synovial Fluid Discriminates Between Juvenile Idiopathic Arthritis and Septic Arthritis

Abstract: Despite their distinct etiology, several lines of evidence suggest that innate immunity plays a pivotal role in both juvenile idiopathic arthritis (JIA) and septic arthritis (SA) pathophysiology. Indeed, monocytes and dendritic cells (DC) are involved in the first line of defense against pathogens and play a critical role in initiating and orchestrating the immune response. The aim of this study was to compare the number and phenotype of monocytes and DCs in peripheral blood (PB) and synovial fluid (SF) from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…However, in the peripheral blood of mice, they are classified according to the expression of Ly6C and CD43: the classical (Ly6C ++ CD43 + ), the intermediate (Ly6C ++ CD43 ++ ), and the nonclassical (Ly6C + CD43 ++ ) ( 40 , 42 ). Based on this theory, it has been proposed that: the classical monocytes are the main origin of osteoclasts (differentiation under normal circumstances); in inflammatory environment, the intermediate monocytes are transformed into osteoclasts with high absorption potential; the non-classical monocyte differentiate into non-resorbable osteoclasts ( 43 46 ). These indicate that the monocytes/macrophages subpopulation is the determinant of the formation and function of osteoclasts, which needs further research to clarify.…”
Section: The Macrophage-osteoclast Axismentioning
confidence: 99%
“…However, in the peripheral blood of mice, they are classified according to the expression of Ly6C and CD43: the classical (Ly6C ++ CD43 + ), the intermediate (Ly6C ++ CD43 ++ ), and the nonclassical (Ly6C + CD43 ++ ) ( 40 , 42 ). Based on this theory, it has been proposed that: the classical monocytes are the main origin of osteoclasts (differentiation under normal circumstances); in inflammatory environment, the intermediate monocytes are transformed into osteoclasts with high absorption potential; the non-classical monocyte differentiate into non-resorbable osteoclasts ( 43 46 ). These indicate that the monocytes/macrophages subpopulation is the determinant of the formation and function of osteoclasts, which needs further research to clarify.…”
Section: The Macrophage-osteoclast Axismentioning
confidence: 99%
“…On the basis of CD14 and CD16 antigens expression, monocytes are divided into three groups: classical (CD14 ++ CD16 − ), intermediate (CD14 ++ CD16 + ), and nonclassical (CD14 + CD16 ++ ) (29,30). According to this hypothesis, classical monocytes are the major source of osteoclasts, while intermediate monocytes can transform into high-absorption-capacity osteoclasts during inflammation, with non-classical monocytes evolving into non-resorbable osteoclasts (31)(32)(33)(34). The study has reported that the intermediate monocytes convert into M1macrophages to perform crucial functions in inflammation of the synovium.…”
Section: The Monocyte/macrophage Origin Of Osteoclastsmentioning
confidence: 99%
“…To fill this gap in knowledge, we have comprehensively profiled monocytes and cDC subsets in the exudate derived from the inflamed joint of JIA patients. Although SF from the joints of arthritis patients, may not be a complete reflection of the inflammation taking place in the tissue, it has proven to be an excellent model to study APC in a highly inflammatory environment 7,21 . Our findings show that at the site of inflammation, there is specific, functional programming of human DC subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Although the maintenance of DC subsets is undergoing consistent dynamic change, monocytes, conventional DC (cDC) and plasmacytoid DC (pDC) are widely accepted as the most dominant APCs in steady state peripheral blood (PB) [4][5][6] . The PB DC subsets are defined as CD141 + cDC1, CD1c + cDC2 and CD123 + pDCs 7 . DCs are also present in tissues where they display a more mature phenotype than their blood counterparts 8,9 .…”
Section: Introductionmentioning
confidence: 99%